Digital Teaching Materials for Poetry Texts in Junior High School: Its Impact on Student's Ability to Understand Poetry Elements - Wasniah Wasniah; Dede Endang Mascita (MASI Mandiri Edukasi, 2025)
Students' learning activities require comprehensive teaching materials to achieve optimal learning outcomes. Teachers and students often need supplementary resources to deepen their understanding of poetic elements in poetry learning. This study aims to describe the core elements of poetry—imagery, diction, and figure of speech—found in Emha Ainun Nadjib’s anthology 99 Untuk Tuhanku, and their utilization in developing digital teaching materials for eighth-grade junior high school students. This research adopts a qualitative descriptive approach involving stages of data reduction, data presentation, and conclusion drawing. Expert lecturers, IT specialists, and Indonesian language teachers validated the developed materials. The validation results indicate a high feasibility level, with an average score of 96.66%. The digital materials were then implemented in classroom learning, and the results showed a significant improvement in students’ understanding of imagery (88%), diction (89%), and figures of speech (91.5%). These findings demonstrate the effectiveness of integrating literary analysis with digital teaching innovations to enhance students’ literary comprehension. The study enriches digital-based literary instruction and offers a model for future teaching material development in language education.